Teachers’ Perspectives on Contextual Teaching and Learning English Approach - Apria Putri Paskah Palawa; Inggrid Yohana Rawung (Sintuwu Maroso Journal of English Teaching, 2022)
This study aims to determine the Teacher's Perspective on Contextual Teachingand learning English Approach. This research is a qualitative research, collect the data using the triangulation method of observation, interviews, and documentation. Analyzing data by making observation sheets of teacher learning activities, to better complement the data from Researcher observations using interviews with the number of questions 5 items. The results of the research from the teacher's perspective on the CTL approach are that the teacher understands the basic concepts and meaning of the CTL approach, by looking atthe results of observations and interviews of researchers, the first teacher and the second teacher make a learning approach according to the CTL learning approach method.